The Effect Of Self-Efficacy And Self-Regulated Learning On Student's Creativity In Biology Practicum - Putri, Sheilla; Tambunan, Efrida Pima Sari (Universitas Labuhanbatu, 2023)
The aim of this research is to determine whether self-efficacy and self-regulated learning can influence creativity either partially or separately or simultaneously. The population used during the research was classes XI and XII MIPA by taking a sample of 35% of the total population. The research method uses a quantitative method, the Ex Post Fact model. Data analysis techniques were carried out using SPSS with the Classical Assumption Test stages such as Normality Test and Multicollinearity Test. Followed by Hypothesis testing such as Partial Test (T-Test), Simultaneous Test (F-Test), along with the Determination Coefficient R2. Then the hypothesis test is determined using the Ho criterion; There is no influence of self-efficacy or self-regulated learning on creativity. Ha; There is an influence of self-efficacy and self-regulated learning on creativity. The final conclusion of this research is that the results of simultaneous testing with an f-count value of 22.785 are greater than the f-table with a 5% significance level of 3.16 (22.785>3.26) and from these results it can be explained that self-efficacy and self-regulated learning influences student creativity